Role of environmental enrichment on social interaction, anxiety, locomotion, and memory in Wistar rats under chronic methylphenidate intake - Herrera-Isaza, Laura; Zárate-Guerrero, Santiago; Corredor, Karen; Gómez-Fonseca, Ángela; Escobar-Cornejo, Guillermo; Cardenas, Fernando P. (Frontiers in Behavioral Neuroscience, 2023)
Chronic use of various compounds can have long-lasting effects on animal behavior, and some of these effects can be influenced by the environment. Many environmental enrichment protocols have the potential to induce behavioral changes. The aim of the present study was to investigate how environmental enrichment can mitigate the effects of chronic methylphenidate consumption on the behavior of Wistar rats. The animals were housed for 20 days under either an environmental enrichment protocol (which included tubes of different shapes) or standard housing conditions. After seven days, half of the rats received 13 days of oral administration of methylphenidate (2mg/kg). After seven days, the rats underwent behavioral tests, including the elevated plus maze (anxiety), open field (locomotion), object-in-place recognition test (spatial memory), and a test for social interaction (social behavior). The results showed that the enriched environmental condition reversed the enhanced time in the open arms of the elevated plus maze induced by methylphenidate (F[1,43] = 4.275, p = 0.045). Methylphenidate also enhanced exploratory rearing in the open field (F[1,43] = 4.663, p = 0.036) and the time spent in the open area of the open field (H[3] = 8.786, p = 0.032). The enriched environment mitigated the inhibition of social interaction with peers induced by methylphenidate (H[3] = 16.755, p < 0.001) as well as the preference for single exploratory behavior (H[3] = 9.041, p = 0.029). These findings suggest that environmental enrichment can counteract some of the effects of methylphenidate. These results are relevant for the clinical treatment of the long-lasting secondary effects associated with methylphenidate pharmacological treatment.